THE PATH TO RECOVERY: BUILDING STUDENT RESILIENCE THROUGH GRATITUDE AND FORGIVENESS - Amien Wahyudi; Agus Supriyanto; Finda Pensiuna Wati; Falama Sheza Insani (Universitas Muhammadiyah Lampung, 2026)
This quantitative study aimed to examine the influence of Gratitude and Forgiveness on Resilience among Muslim students in Yogyakarta. This issue is important given the high stressors faced by students and the need to identify protective factors. The study involved 331 Muslim students who completed the Gratitude Questionnaire-Six Item Form (GQ-6), the Heartland Forgiveness Scale (HFS), and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). Data were analyzed using multiple regression analysis. The results indicated that Gratitude, both simultaneously and partially, had a significant and positive influence on Resilience. Together, the two variables explained 22.2% of the variability in Resilience. Interestingly, Forgiveness exhibited a slightly greater predictive power compared to Gratitude, a theoretical contribution that suggests the vital role of religious values within the subjects' cultural context. Although this finding enriches the study of positive psychology in Indonesia, the limitation of the cross-sectional design prevents the establishment of causality. Practically, the findings recommend that Guidance and Counseling services design interventions focused on Gratitude training (gratitude journaling) and Forgiveness (self-forgiveness and conflict resolution) as an applied strategy to enhance students' psychological adaptation and resilience.